PENGARUH GAME EDUKASI WORDWALL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 231 PALEMBANG - Pani Anista; Neta Dian Lestari; Tanzimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Wordwall educational game on the mathematics learning outcomes of fifth-grade students at SD Negeri 231 Palembang. The method used in this research is an experimental method with a true experimental pretest-posttest control group design. The study consists of two groups: a control group that did not use the Wordwall educational game and an experimental group that used the Wordwall educational game during the learning process. Data collection was carried out using tests to measure students' learning outcomes, which were administered during both the pretest and posttest.Based on the results of hypothesis testing using an independent sample t-test, the posttest score of the control group was 55.22, while the experimental group scored 78.26. According to the SPSS output of the hypothesis test, the obtained t-value was 5.688, which is greater than the t-table value of 0.297, with a significance level of 0.000 < 0.05. This indicates that the use of the Wordwall educational game has a significant effect on the mathematics learning outcomes of fifth-grade students at SD Negeri 231 Palembang.